Cornered - Lynn, Barry C. (Hoboken, N.J. : John Wiley & Sons, 2010)
Journalist Barry C. Lynn paints an alarming picture: most of our public debates about globalization, competitiveness, creative destruction, and risky finance are nothing more than a cover for the widespread consolidation of power in nearly every sector of the American economy.
The hidden monopolies everywhere -- Supply and command -- The crystal house -- The market masters -- In the cockpit -- Lightning escapes the bottle -- The American piece -- Wreckonomics 101 -- To keep our republic.
Keywords: Monopolies; Capitalism